2016
DOI: 10.1038/ismej.2016.20
|View full text |Cite
|
Sign up to set email alerts
|

Diverse, uncultivated bacteria and archaea underlying the cycling of dissolved protein in the ocean

Abstract: Dissolved organic nitrogen (DON) supports a significant amount of heterotrophic production in the ocean. Yet, to date, the identity and diversity of microbial groups that transform DON are not well understood. To better understand the organisms responsible for transforming high molecular weight (HMW)-DON in the upper ocean, isotopically labeled protein extract from Micromonas pusilla, a eukaryotic member of the resident phytoplankton community, was added as substrate to euphotic zone water from the central Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
138
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(152 citation statements)
references
References 109 publications
(132 reference statements)
11
138
0
Order By: Relevance
“…An example of a bacterial group enriched in the small size‐fractions is that of the Oceanospirillales SAR86. This clade has been reported to be present in distinct size‐fractions, yet be more abundant and active in the smallest one (Orsi et al., ), in agreement with what we observed. Contrarily, Planctomycetes represent a group which is highly enriched in the larger particle size‐fractions independent of depth (e.g., Crespo et al., ; Ganesh et al., ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…An example of a bacterial group enriched in the small size‐fractions is that of the Oceanospirillales SAR86. This clade has been reported to be present in distinct size‐fractions, yet be more abundant and active in the smallest one (Orsi et al., ), in agreement with what we observed. Contrarily, Planctomycetes represent a group which is highly enriched in the larger particle size‐fractions independent of depth (e.g., Crespo et al., ; Ganesh et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, we observed a distinct distribution of the Acidimicrobiales (Actinobacteria) with depth: whereas the family “OCS155 marine group” predominated in the sunlit layers and was enriched in small size‐fractions, the family “Sva0996 marine group” predominated in the dark layers and was enriched in the 5.0–10 μm particle size‐fraction. Therefore, although members of the Acidimicrobiales have been described mainly as free‐living microbes prevalent at the DCM (Mizuno, Rodriguez‐Valera, & Ghai, ) where they actively recycle proteins (Orsi et al., ), some families can be enriched in aphotic waters, in particular in the larger particle size‐fractions.…”
Section: Discussionmentioning
confidence: 99%
“…CPC OTU #5, which is phylogenetically related to Coraliomargarita akajimensis DSM45221 in the family Puniceicoccaceae and the phylum Verrucomicrobia, was the one of the dominant taxa in both the PAB and FLB communities (Figure ). The phylum Verrucomicrobia is an important group for mediating the cycling of dissolved organic nitrogen onto and off particles (Orsi et al., ). Herleman et al.…”
Section: Resultsmentioning
confidence: 99%
“…According to Orsi et al. (), the Verrucomicrobia have a relatively strong preference for consuming dissolved proteins (0.2–0.8 μm) compared with other bacterial groups such as the Actinobacteria, Flavobacteria, Alphaproteobacteria, Gammaproteobacteria, etc. This may explain the increased abundance of CPC OTU #5 in only the FLB community despite the concentration of HMW organic compounds being relatively high in the microenvironment of the PAB community.…”
Section: Resultsmentioning
confidence: 99%
“…Microbial communities of all three domains also differed between sea water samples and sediment trap (particle interceptor traps) contents (Fontanez et al, 2015). In a study employing stable isotope probing, specific particle-associated clades were identified that specialize in the degradation of highmolecular weight compounds (Orsi et al, 2016). Recently, Pernice et al (2016) described a highly variable eukaryotic microbial community composition that was affected by depth, water masses, as well as the number of prokaryotes.…”
Section: Introductionmentioning
confidence: 99%